Altered DNA repair capacity and bleomycin sensitivity as risk markers for non‐small cell lung cancer - Rajaee-Behbahani, Nahid; Schmezer, Peter; Risch, Angela; Rittgen, Werner; Kayser, Klaus; Dienemann, Hendrik; Schulz, Volker; Drings, Peter; Bartsch, Helmut (International journal of cancer, 2001)
DNA repair capacity in human peripheral blood lymphocytes was monitored by the repair rate of bleomycin‐induced DNA damage using an alkaline single‐cell gel electrophoresis assay (comet assay).